Cyr61 Mediates Angiotensin II-Induced Podocyte Apoptosis via the Upregulation of TXNIP. (29th March 2023) - Ma, Jingxue; Ma, Ruiying; Zhao, Xiaoyue; Wang, Yingxiu; Liao, Shengxue; Nong, Cong; Lu, Fengling; Liang, Zhao; Huang, Junhui; Huang, Yan; Zhu, Zhengxi; Wang, Junjie
Abstract : Purpose . It is well documented that angiotensin II (Ang II) elevation promotes apoptosis of podocytes in vivo and vitro, but the potential mechanism is still oscular. The current study is aimed at probing into the assignment of cysteine-rich protein 61 (Cyr61) in Ang II-induced podocyte apoptosis. Methods . Podocytes were treated with Ang II (10 -6 mol/L) for 48 hours to establish an injury model in vitro. Western blot assays were detected the expression of Cyr61, Cyt-c, Bax, and Bcl-2. Gene microarray was used to analyze the expression of mRNAs after treatment with Ang II. CRISPR/Cas9 technology was used to knock down Cyr61 and overexpress TXNIP gene, respectively. Results . The expression of Cyr61, TXNIP, Cyt-c, and Bax in podocytes treated with Ang II were upregulated, but the expression and apoptotic rates of Bcl-2 in podocytes were inhibited. The level of the above factors was not significantly different after the knockdown of Cyr61 with Ang II in podocytes. In Ang II group, when knocked down Cyr61, the expressed level of TXNIP, Cyt-c, and Bax was diminished after Ang II treatment; interestingly Bcl-2 expression and podocyte apoptotic rate were reduced. Under the stimulation of Ang II, the expression of Cyt-c and Bax were growing, whereas Bcl-2 was reduced, and the apoptotic rates were higher in the TXNIP overexpression group. Cyt-c and Bax were put on, whereas that of Bcl-2 was to be cut down when the Cyr61 was knockdown, and the apoptotic rates were gained in the TXNIP overexpression+Cyr61 knockdown group. Conclusions . The results of the study extrapolate that Cyr61 plays a dominant role in Ang II-induced podocyte apoptosis. Additionally, Cyr61 may mediate the Ang II-induced podocyte apoptosis by promoting the expression of TNXIP.